Active Ga-catalysts for the ring opening homo- and copolymerization of cyclic esters, and copolymerization of epoxide and anhydrides. Issue 38 (23rd September 2020) - Ghosh, Swarup; Glöckler, Eduard; Wölper, Christoph; Tjaberings, Alexander; Gröschel, André H.; Schulz, Stephan
Abstract : Ring opening homo- and copolymerization of lactide (LA) and ε-caprolactone (ε-CL) in solution with several Ga catalysts yielded isotactic-enriched PLAs and well defined diblock copolymers by coordination insertion mechanism (CIM). Abstract : A series of gallium complexes L 1 2 Ga4 Me8 (1 ), L 2 2 Ga4 Me8 (2 ), and L 3 2 Ga4 Me8 (3 ) was synthesized by reaction of GaMe3 with Schiff base ligands L 1–3 H2 (L 1 H2 = 2, 4-di- tert -butyl-6-{[(3-hydroxypropyl)imino]methyl}phenol; L 2 H2 = 2, 4-dichloro-6-{[(3-hydroxypropyl)imino]methyl}phenol; L 3 H2 = 4- tert -butyl-2-{[(3-hydroxypropyl)imino]methyl}phenol) and characterized by 1 H, 13 C NMR, IR spectroscopy, elemental analysis and single crystal X-ray analysis (1, 2 ), proving their tetranuclear structure in the solid state. Complexes 1–3 showed good catalytic activity in the ring opening homopolymerization (ROP) and ring opening copolymerization (ROcoP) of lactide (LA) and ε-caprolactone (ε-CL) in the presence of benzyl alcohol (BnOH) in toluene at 100 °C, yielding polymers with the expected average molecular weights ( M n ) and narrow molecular weight distributions (MWD), as well as a high isoselectivity for the ROP of rac -lactide ( rac -LA), yielding isotactic-enriched PLAs with P m values up to 0.78. Kinetic studies with complex 1 proved the first order dependence on monomer concentration, while mechanistic studies confirmed the coordination insertion mechanistic (CIM) pathway. Sequential addition of monomers gave well defined diblock copolymers of PCL- b -PLLA and PLLA- b -PCL, proving the living character of the polymerization reactions. The catalysts also showed perfect selectivity for the copolymerization of cyclohexene oxide (CHO) with both succinic anhydride (SA) and maleic anhydride (MA) in the presence of BnOH and produced >99% alternating block copolymers.